Storage Properties of Gamma-Irradiated Semi-dried Fish Varieties - P.Q., Vinh; M.D., Alur; P.M., Nair (Fishery Technology, 2025)
Several varieties of semi-dried unirradiated and irradiated (1&3 kGy) fish, namely, anchovies (Stolephorus commersonii), Bombay duck (Harpodon nehereus), shrimp (Penaeus indicus) and Vietnam scad (Alepes mate) were stored at ambient temperature (26Â°C). During the course of storage, quality characteristics such as total bacterial count (TBC), mould count and biochemical indices of freshness were studied. These studies indicated that initial TBC of semi-dried fish varied from 7(1)-54(X) cfu per g of fish, while mould count ranged from 27-15(X) cfu per g. llowever, upon irradiation at 3 kGy, initial bacterial load was considera bly reduced. Vietnam scad was not contaminated with mould after 35 months of storage at room temperature. Indices such as TVA and TVBN increased during storage at room temperature for both unirradiated and irradiated samples.